Impact of Temperature on the Growth Performance, Survival Rate, Osmoregulation, Dissolved Oxygen and Physiological Changes of Freshwater Tilapia (Oreochromis mossambicus) - V. K., Remya; Cheruparambath, Praseeja; B., Sreelekha; U., Vijayalekshmi; Banu, C. Ayisha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
For many aquatic species, any changes in water temperature affect their survival. This study was performed to investigate the effect of rising temperature on the growth parameters, protein content, dissolved oxygen content, moisture content osmoregulation, and physiological activity of freshwater Tilapia (Oreochromis mossambicus). The experiments were set in plastic fish tanks, the experimental tank placed in direct sunlight and the control tank in shade, and measuring temperature and pH daily, with proper aeration and feed was provided. The study found that increasing water temperature led to higher mortality rates and low survivability percentages in fish, with a higher growth rate in the experimental group with a pH range of 5.7 to 8.2. High dissolved oxygen levels were recorded during the experimental period, with a mean difference of 26.56 compared to the control group, possibly causing restless movement in fish. The study revealed that the alkalinity of water decreases with increasing temperature. The study found that increased salinity led to a significant increase in growth performance, indicating an increase in metabolic rate, and a decrease in alkaline nature. The difference between the mean protein value in the experimental and control groups is 0.896mg/ml. Thermal limitations may negatively impact O. mossambicus physiological responses, impacting aquaculture production due to predicted global climate change-induced water temperature changes.